International Trade Law and the World Trade Organization: Promoting Global Economic Cooperation - Atiyat , Mustafa Al; AlDweri, Khalid; Alsoud, Anas Ratib (Journal of Ecohumanism, 2024)
International commerce has emerged as a key EG driver in our more interconnected world, boosting both national prosperity and individual well-being. This study intends to investigate how the World Trade Organization (WTO) and international trade law (ITL) are related and what function they play in fostering international economic cooperation. Data collection and analysis will be done using a quantitative research approach. The data collection strategy will involve the creation and distribution of online surveys to individuals interested in ITL and the WTO. The survey questionnaire will encompass inquiries about various aspects, including the impact of ITL on economic cooperation, the effectiveness of the WTO's policies, and other relevant variables. A sample size of 600 individuals, who are knowledgeable about or involved in ITL and the WTO, will be selected. Statistical analysis programs like SPSS will be used to analyze the data from the online surveys. The data will be employed to examine the relationship between ITL, the WTO, and their influence on global economic cooperation. The collected data through the questionnaire will be instrumental in achieving the objectives of this research study. The 600 questionnaires distributed were arranged in the form of a Likert Scale. This information will be gathered in order to better understand how ITL and the WTO affect international economic cooperation by shedding light on their respective contributions to that cause.